Regional Autonomy in Indonesia after the Second Constitutional Amendment: Assessing its Developmental Delivery - Mendy, Ousu (Fakultas Hukum Universitas Lampung, 2024)
As regional autonomy through decentralization becomes increasingly prevalent worldwide, it has also been enshrined as a constitutional principle in Indonesia. This approach was adopted following constitutional amendments aimed at shifting authority from the national to the local level, with the intention of enhancing governance quality and standards. Indonesia has implemented a thorough decentralization strategy since the late 1990s, granting subnational governments the autonomy to select programs that better address community needs and regional development goals. This research seeks to evaluate the extent to which regional autonomy has achieved its objectives. To accomplish this, a normative research method is employed, utilizing secondary sources such as journal articles, books, newsletters, and other relevant materials. The research concludes that regional development strategies have not met public expectations and suggests that efforts should focus on reducing significant disparities in social and economic opportunities across the country, as well as improving incomes and living standards in the regions through regional autonomy. This could be pursued through judicial review of laws related to regional autonomy.